Sistema autônomo tri-banda de aquisição e armazenamento de dados para caracterização de paisagem acústica submarina - Buchmann, Rafael Mazza (2017)
This work presents a study of the acoustic landscape of the oceans, focusing mainly on the understanding of the acoustic signal physics in the marine environment, how to measure it and characterize some sources, such as mammals and ships. Knowing the signal to be measured, an autonomous data acquisition system for hydrophones was designed, capable of acquiring, conditioning and storing data using a microcontrolled system. As a project differential, a tri-band filter was developed, aiming to separate the frequency bands (low-pass, band-pass and high-pass filters), including amplifiers with gain adjustable through the microcontroller. Based on the design, a prototype was built, its features were obtained through bench tests and its performance tested in a hydrophone calibration tank. The manufacturing and testing of the prototype made possible to carry out another step in the search for a system to be industrialized, contributing to the research and development in Brazil.